The evolution of Genetic Molecular Map and phylogenetic tree of Coronavirus (COVID-19) - AL-Mutar, Hayder A. H. (The Iraqi Journal of Veterinary Medicine, 2020)
Coronavirus (COVID-19) is suspected to originate from an animal host (zoonotic) followed by a human to human transmission, The purpose of the present study is to determine the genetic affinity of a phylogenetic tree and conformation of protein between human and bat. Through study of genetic sequencing, as shown in the tree design of strains and genetic variants, the main cause of COVID-19 is the Bat Coronavirus RaTG13 (SARS) virus in ID: MN996532.1 and ID: MG772933.1 (24-Jul-2013 and Feb-2017) shows that the evolution of the Corona virus from 2003, 2013 to 2020 which has become the most deadly peak in humans, the virus evolved from the bat effect on Humans. Protein analysis show 98 change of amino acid form RaTG13 (SARS) virus to COVID-19 Homo sapiens. Consequently, this study increased our understanding of the genetic variety of the COVID-19 carried by bats. So we conclude that a protein conformation drawing shows high identity compatibility between a bat and a human